Microwave pretreatment effects on switchgrass and miscanthus solubilization in subcritical water and hydrolysate utilization for hydrogen production. (January 2018) - Irmak, Sibel; Meryemoglu, Bahar; Sandip, Anjali; Subbiah, Jeyamkondan; Mitchell, Robert B.; Sarath, Gautam
Abstract: Microwave pretreatment is an energy-efficient and environmentally benign technology that can be used to reduce the recalcitrance of complex biomass structure. Switchgrass ( Panicum virgatum L.) and miscanthus ( Miscanthus x giganteus ) are perennial C4 grasses that are being developed as bioenergy crops because they have high yield potential and desirable agronomic traits. These materials are promising candidates for biofuels, bioproducts and green chemicals production from biomass. In the present study, miscanthus and switchgrass biomass were solubilized in subcritical water after pretreatment by microwave at different processing temperatures. The hydrolysates obtained were evaluated for hydrogen-rich gas production by aqueous-phase reforming (APR). Higher temperature microwave processing reduced the biomass recalcitrance resulting in microwave treated materials having 7–10% higher solubility in subcritical water than untreated materials. However, gasification of pretreated biomass hydrolysates produced less gaseous products compared to untreated biomass for both switchgrass and miscanthus. Miscanthus biomass was more vulnerable to destruction by microwave treatment and recalcitrance of this biomass was achieved at lower temperature compared to switchgrass. Miscanthus biomass that was not microwave treated produced the highest gas yield. Microwave pretreatment caused significant increases in the formation of ungasified solid carbon residue in the APR process. Highlights: Miscanthus and switchgrass were pretreated by microwave at different temperatures. Pretreated samples were solubilized in subcritical water. The hydrolysates were evaluated for hydrogen-rich gas production by APR. Pretreatment increased biomass solubility in subcritical water. Pretreatment negatively affected the gasification of both biomass materials.